Role of Community Radio (CR) in climate changes issues in Bangladesh: a case study of Radio Nalta, Kaligonj, Satkhira - Rahman, Md. Mominur (BRAC University, 2014)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2013.